2010
DOI: 10.1161/circulationaha.109.906859
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Therapeutic Hypothermia by Paramedics After Resuscitation From Out-of-Hospital Ventricular Fibrillation Cardiac Arrest

Abstract: Background— Therapeutic hypothermia is recommended for the treatment of neurological injury after resuscitation from out-of-hospital cardiac arrest. Laboratory studies have suggested that earlier cooling may be associated with improved neurological outcomes. We hypothesized that induction of therapeutic hypothermia by paramedics before hospital arrival would improve outcome. Methods and Results— In a prospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
196
2
14

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(215 citation statements)
references
References 24 publications
3
196
2
14
Order By: Relevance
“…Prehospital induction via 4uC normal saline is feasible, safe, and effective in decreasing core temperature. 11,13 However, four prospective randomized trials have found no difference in outcomes with prehospital cooling initiation. 12,14,20,21 In contrast, a retrospective study using ice packs found deleterious effects of every 5-minute delay in TH initiation and every 30-minute delay in time-to-target temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prehospital induction via 4uC normal saline is feasible, safe, and effective in decreasing core temperature. 11,13 However, four prospective randomized trials have found no difference in outcomes with prehospital cooling initiation. 12,14,20,21 In contrast, a retrospective study using ice packs found deleterious effects of every 5-minute delay in TH initiation and every 30-minute delay in time-to-target temperature.…”
Section: Discussionmentioning
confidence: 99%
“…8 Observational human studies, although limited by their design, have also yielded conflicting results, with rapid cooling reported to be associated with improved, neutral, and negative effects on neurologic status and mortality. [9][10][11][12][13][14][15] Despite the lack of clear evidence, many prehospital systems have implemented prehospital cooling protocols for post-cardiac arrest patients who remain comatose in the field. The benefit, if any, of this practice is unknown.…”
Section: Ré Sumémentioning
confidence: 99%
“…Although chilled saline infusions can be used by paramedics to induce therapeutic hypothermia (TH) for post-arrest patients similar to that shown to be effective when started in the ED, implementation studies are still needed to confirm if there is an outcome benefit to starting this in the field. 8 After numerous small studies confirming that TH initiated by EMS is feasible and affordable, a recent trial found that EMS-initiated TH did not result in any long-term benefits for the patient. 9 Since the post-arrest period is a dynamic period where paramedics must monitor and manage a complex patient with limited human and technological resources, removing any unnecessary procedures and distractions should be favored over the implementation of a therapy with no evidence of value.…”
Section: Ems: Translation Challengesmentioning
confidence: 99%
“…Examples of EMS-specific research include therapeutic interventions for cardiac arrest, the use of continuous positive airway pressure for respiratory distress, fibrinolysis for STEMI in rural settings, therapeutic hypothermia for post-arrest, and reducing ED visits for nursing home patients through collaborative models of care. 2,8,9,11,[17][18][19][20][21][22] Similarly, EMS researchers have addressed policy matters, such as termination of resuscitation, hospital bypass, and ED offload delay. 23,24 Workforce issues, such as clinical judgment, workplace violence, and occupational hazards, have also been scientifically investigated.…”
Section: Ems-centred Researchmentioning
confidence: 99%
“…In 2002, 2 key studies 25,26 showed that treatment with 27 and the AHA 28 recommended induced hypothermia in post-cardiac arrest patients with ROSC who remain comatose ( Table 2). Prehospital cooling studies 29,30 have also been performed; however, no clear evidence shows that prehospital cooling is advantageous, and ongoing investigations continue. Induced hypothermia should be initiated to a target temperature of 32ºC to 34ºC as quickly as possible and within 6 to 12 hours for patients who are unable to follow verbal commands after ROSC.…”
Section: Management Of Post-cardiac Arrest Syndromementioning
confidence: 99%